150. Dosimetric verification of stereotactic head treatments performed with Helical Tomotherapy using alanine dosimeters and gafchromic films. (December 2018) - Panzeca, S.; Savoca, S.; Iacoviello, G.; Caputo, V.; Cuccia, F.; Luca, N.; Gallo, S.; Brai, M.; Panese, A.; Marrale, M.
Abstract: Purpose: The aim of this work is the dosimetric verification of stereotactic head treatments performed with Helical Tomotherapy[1] using an anthropomorphic phantom, the Rando Head Alderson, combined with alanine[2] dosimeters and EBT3 gafchromic films[3] . Methods: A CT scan of Rando Head Phantom was used to simulate five different clinical situations regarding "tumor" dimension, position and proximity relations with Organs at Risk (OAR). All five treatment plans were computed using 1 cm beam width, pitch values lower than 0.215 and modulation factor between 1.6 and 2.5. In all cases, the dose constraints required for OAR have been met. During treatment delivery, the alanine dosimeters were placed in the phantom housings to perform dose-specific measurements for either the PTV and OAR, and gafchromic films were inserted between contiguous slices of the phantom to achieve bidimensional dose distributions on the transverse plane. Results: Dose distributions measured by gafchromic films were compared to those calculated using the 3% – 3 mm criterion for the gamma function using the Tomotherapy DQA module. Also the results of point measurements made with alanine agree with the dose values calculated by TPS within the experimental uncertainties. Conclusions: The data show an excellent agreement between calculated and measured dose not only for PTV but also for the OAR, receiving significantly lower doses.